Elevated IL-6 and TNF-α Associated with Treatment-Resistant Depression in Virally Suppressed HIV Patients: A Cross-Sectional Biomarker Study - Wisnu Wardhana Putra; Muhammad Yusuf; Mahmood Abbas; Nadia Khoirina; Felicia Sari; Abdullah Assagaf (HM Publisher, 2025)
Introduction: Despite effective antiretroviral therapy (ART), major depressive disorder (MDD) remains highly prevalent in people living with HIV (PLWH). A subset of these patients develops treatment-resistant depression (TRD), creating a significant clinical burden. The